Comparative influence of kolaviron and coenzyme Q10 on complex I activity, glutamate clearance, 3,4-dihydroxyphenethylamine metabolism, and redox stress in rotenone-induced neurotoxicity (Nigerian Journal of Physiological Sciences, 2022)
3,4-dihydroxyphenethylamine (dopamine) depletion, inhibition of complex I activity, oxidative stress, and glutamate excitotoxicity are cardinal biochemical features of neurotoxicity induced by systemic unilateral infusion of rotenone. Kolaviron (KV), a biflavonoid from Garcinia kola seeds, has been proven to have pharmacological effects against neurotoxicity. Coenzyme Q10 plays an essential role in mitochondrial oxidative phosphorylation and as an antioxidant. This study examined the comparative influence of kolaviron and coenzyme Q10 on complex I activity, dopamine metabolism, glutamate clearance, and redox stress in rotenone-induced neurotoxicity in the cortex, hippocampus, and striatum of the brain of rats. Adult Male Wistar rats were pretreated with 200 mg/kg KV or 100 mg/kg coenzyme Q10 for 7 days followed by administration of a progressive six doses of 1.5 mg/kg rotenone within the next 48 h after which the animals were euthanized and the brain excised. On the cortical, hippocampal, and striatal regions of the brain, complex I activity, dopamine metabolism, oxidative stress markers, as well as glutamate metabolism were carried out and analyzed. In all brain regions examined, KV and coenzyme Q10 pretreatment modulated complex I activity, ameliorated redox imbalance, and enhanced dopamine metabolism via increasing the activity of tyrosine hydroxylase and decreasing monoamine oxidase activity. KV facilitated glutamate clearance through augmentation of glutamate dehydrogenase and glutamine synthetase activities.  The activity of KV was comparable to that of the mitochondrial membrane antioxidant compound, coenzyme Q10, this indicates that KV is a promising therapeutic agent in the treatment of Parkinson’s disease and its activity compares well with coenzyme Q10